Complete framework of wind-vehicle-bridge interaction with random road surfaces. (13th October 2019) - Camara, A.; Kavrakov, I.; Nguyen, K.; Morgenthal, G.
Abstract: The risk of vehicle accidents and discomfort under wind actions is key in the serviceability assessment of long-span bridges. This paper presents a complete wind-vehicle-bridge interaction (W-VBI) framework in which the pavement irregularities are simulated as random surfaces that include the bridge joints instead of traditional one-dimensional (1D) road profiles. The methodology includes a new approach to assess the safety and comfort of all the users of the bridge, including those in the vehicles and on the deck, and to account for the variability of the response. The application of the proposed W-VBI framework in the study of a long cable-stayed bridge demonstrated that the driving safety and the pedestrians' comfort cannot be based on the analysis of a single record, and guidance is proposed to obtain results with statistical significance. Moreover, it is observed for the first time that 1D road irregularity models can significantly underpredict the risk of discomfort and of driving instabilities in bridges subjected to crosswinds. Finally, the direct connection between the quality of the road and the comfort in the vehicles is clearly established, which has potential implications on pavement monitoring programmes.